Quality of biology laboratory infrastructure and Facilities in High School - Sekar Ganda Ning Tyas Arum; Much Fuad Saifuddin; Silfi Pratiwi; Tri Rahayu Isnayanti; Dinda Iftiqa Rahma; Etika Dyah Puspitasari; Retno Wulandari; Purwanti Pratiwi Purbosari (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2024)
Practicum is one of the essential learning activities for students psychomotor and fosters scientific attitudes in students. Therefore, adequate laboratory infrastructure is needed. Biology laboratory standards are contained in the regulation of the Minister of national education No. 24 of 2007 concerning Standards for Educational Facilities and Infrastructure. The research as descriptive qualitative was conducted at School A, School B, and School C with data collection techniques using observation and interviews. The study results indicate that laboratory facilities and infrastructure, including infrastructure, facilities and Biosecurity Level 1, follow the standards set in the regulation of the Minister of national education No. 24 of 2007. Based on the research that has been done, the most suitable facilities and infrastructure according to the standards of regulation of the Minister of national education No. 24 of 2007 are School B. Fulfillment of standards can support the smooth running of practicum. Besides, schools must keep raising standards to a higher level.